Additional Freeze Drying Fig Fruit (Ficus Carica L) Filtrate into Tris Egg Yolk Extender and Its Effect on Sperm Membrane Integrity and Acrosome of Kacang Buck - Zaenuri, Lalu Ahmad; Lukman, Lukman; Yanuarianto, Oscar; Sumadiasa, I Wayan Lanus; Rodiah, Rodiah (ANIMAL PRODUCTION, 2017)
A study was designed to determine Kacang buck sperm membrane integrity and acrosome reaction as to the effect of different concentration of freeze drying fig fruit filtrate in tris egg yolk based extender. This study used 5 proven fertility Kacang goats aged 3-4 years, maintained by Faculty of Animal Sciences, Mataram University, Indonesia. Semen was collected by artificial vagina at every five days. The collected semen was divided into four aliquots in accordance to the treatments extender such as Control (0 gr), T1 (0.02 gr), T2 (0.04 gr) and T3 (0.06 gr) freeze drying fig fruit filtrate in tris egg yolk based extender (gr/v), respectively. Plasma membrane integrity and intact acrosome after re-concentration and preserved at 5ºC were assessed visually at 0 and every 24 hours for 5 consecutive days. The statistical significance of the result was evaluated by a one way ANOVA for completely randomized design analysis of variance. Data were presented as Mean±SD. Results suggest that the mean percentages of sperm membrane integrity in T0, T1,T2 and T3 at 96 h post extended and preserve at 5ºC were 34.3±5.3,  40.6±4.7,  44.8±5.4 and  42.1±5,1, respectively. The mean percentages of sperm acrosome intact were 16.4±4.8, 18.5±1.9,  21.6±3.1 and 19.6±2.8, respectively. The results of the study suggested that additional 0.04gr freeze drying fig fruit filtrate into tris egg yolk based extender have a significant preservation effect on both spermatozoa membrane integrity and acrosome intact of kacang buck.